PENGARUH LAMA PAPARAN SINAR UV TERHADAP PENURUNAN TOTAL COLIFORM PADA AIR BERSIH DI PT.Yz (Jurnal Kesehatan Siliwangi, 2021)
PT.Yz is one of the leather tanning industries that providesclean water for hygiene and sanitation activitiesfor employees.The total amountof Coliform in clean water at PT. Yz does not meet the quality standard requirements,namely 547.3/100ml.Thisresearch is experiental with a prepost  test without control design, namely with 2 treatmentsof UV exposure time of 30 seconds and 60 seconds with many repetitions 9 times.The number of samples used are 27 samples with 2.7 liters of clean water. The sampling technique used is grab sampling. The population is all clean water at PT.yZ, the sample is part of clean water used for domestic needs,Add a collection tool The data are a set of laboratory tools and a pHmeter.Univariate and Bivariate Independent t-test data analysis test. The results showedthe effect of exposure time of 30 seconds and 60   seconds can reduce the numberof Coliform bacteria. The results of the Independent t-test test, P value 0.027 <0.05, which means that there is a difference in the length of time exposure to UV light todecrease thenumber of Coliform bacteria in clean water.Furtherres earchers are advised to use a longer exposure time with the same UV light anddoitcontinuously